REVITALISASI ETIKA BISNIS DALAM MEMBANGUN SISTEM PEREKONOMIAN YANG BERADAB - Mu'min, Ma'mun (BISNIS, 2015)
The  revitalization  of  business  ethics  in  the  global  economic  system  today urged   to   be   done   given   the   global   economic   competition   tend   to justifies  any  with  regard  not  business  ethics.  Business  Ethics  so  very important  done  especially  in  arranging  business  relationship  with  the parties  that  are  related  with  good  nature,  environment,  companies and  individuals.  Do  business  with  regard  not  the  ethics  of  course  willresult  in  injustice,  evil  and  destruction,  or  at  least  no  parties  who  are disadvantaged  because  of  the  fraudulent  behavior.  The  revitalizationof  business  ethics  in  order  to  build  the  economy  that  civilized  so urgent   and   urgent.   Among   the   business   ethics   that   must   be   were revitalized,    namely    values    of    honesty,    trust    responsible,    moral courage, fairness, realistic and critical, humble respect for  stakeholders.